Edukasi Pemanfaatan Buah Pedada (Sonneratia caseolaris) Menjadi Selai Sehat dengan Pemanis Stevia sebagai Produk Olahan Mangrove: Education on the Utilization of Pedada Fruit (Sonneratia caseolaris) into Healthy Jam with Stevia Sweetener as a Mangrove Processed Product - Marjanah; Indriaty; Wahyuni, Ayu (Universitas Mataram, 2025)
Abstract: One form of utilization of aquatic resources is mangrove forest vegetation. The potential of mangroves in Indonesia is very large because it has several types of mangroves that thrive. Pedada fruit (Sonneratia caseolaris) is one type of mangrove fruit that grows abundantly throughout the coastal areas of Langsa-Aceh. The business of processing mangroves into food products has not been widely developed and is of interest to coastal communities. One of the processed foods made from jam can be made from the heating process of a mixture of fruit pulp and sugar. Pedada fruit can be processed into a healthy jam by reducing sugar in the processing process which is replaced with stevia. The process of making jam from pedada fruit (Sonneratia caseolaris) with the addition of stevia sweetener begins with cleaning the material, namely pedada fruit. The next process is mixing the pulp of the pedada fruit and adding stevia sugar, then the heating, thickening and cooling process is carried out. The process ends with packaging. The production of healthy jam from pedada fruit can improve the economy of the community. Therefore, the PKM Team of Samudra University wanted to help the economy of Biruen residents by making education on processing pedada fruit into healthy jam. The hope is that the pedada fruit jam product can become a new business for the community and can increase the UMKM of the Bireum community. This is the background for the PKM Team of Samudra University to create education on making healthy jam with the addition of stevia. Keywords: community service, healty jam, pedada fruit, stevia